Selecting general entities for TOGAF’s core content metamodel using best worst method - Zuliansyah, Mochammad; Desa, Mohammad Ishak; Ahmad, Sabrina (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Enterprise Architecture (EA) Developments are often faced with metamodel complexity problem. The data for metamodel exploration significantly affects the depth of an EA analysis. In practice, however, it is limited by the scope, cost, time and quality. The entities in the EA initiation metamodel is crucial in forming an optimal metamodel based on data completeness, time, cost, quality, and scope. In this study, entities in the EA metamodel were selected from general entities in the TOGAF's core content metamodel, combined with various standards related to the upstream petroleum industry. The entity selection methodology consists of two stages, namely Preparation and Screening, as well as Analysis and Selection. Entity data are extracted from the needs of the upstream petroleum industry. The analysis was done using the best worst method (BWM). The criteria are based on the EA development goals of the Federation of Enterprise Architecture Professional Organizations. BWM analysis produces a relatively meaningful ranking of the entities that forms as general entities in the core content metamodel. This study proposes the methodology, ranking order of entities, and entities composition that form general entities for the core content metamodel.